Peningkatan Kemampuan Pemecahan Masalah Matematika Siswa Melalui Model Pembelajaran Laps-Heuristik Berbantuan Edutainment di SMA Negeri 1 Tarabintang - Sinarta Pintauli; Erlinawaty Simanjuntak (Journal on Education, 2023)
This study aims to determine the increase in mathematical problem-solving abilities by applying the Edutainment assisted LAPS-Heuristic learning model. This type of research is PTK, with a qualitative approach. The research consisted of pre-cycle activities, cycle 1 and cycle 2. The research subjects were 23 students in class X Mia at SMA Negeri 1 Tarabintang TA.2021/2022. Pre-cycle, students who complete 34.79%, who do not complete 65.21%. Cycle 1 of students who completed 74%, who did not complete 26%. Cycle 2 of students who completed 91.30%, and who had not completed 8.70%. The application of the LAPS-Heuristic learning model can improve students' mathematical problem-solving skills in trigonometry material